106k views
3 votes
Multiply the binomials useing the FOIL method and simplify.

(b-3)(b+9)

A. b²-27
B. b²+12b-27
C. b²+6b-27
D. b²-6b-27

2 Answers

7 votes
The foil method is the same as the method I've been showing you, except in a certain order (Firsts, Outsiders, Insiders, Lasts), so:
(b - 3)(b + 9)
Firsts: b × b = b^2
Outsiders: b × 9 = 9b
Insiders: -3 × b = -3b
Lasts: -3 × 9 = -27
So in total you get b^2 + 6b - 27, which is answer C. I hope this helps!
User Kereem
by
6.0k points
1 vote
(b-3)(b+9)
b^2+9b-3b-27
b^2+6b-27
User Fudu
by
5.6k points